Black Seed Thymoquinone Improved Insulin Secretion, Hepatic Glycogen Storage, and Oxidative Stress in Streptozotocin-Induced Diabetic Male Wistar Rats - Tag, Hend M.; Muhammad, Muhammad A. A.; Kilany, Omnia E.; Abdelrazek, Heba M. A.; Abdelazim, Aaser M. (Oxidative medicine and cellular longevity, 2018)
Diabetes mellitus is one of the metabolic diseases having several complications. Nigella sativa oil (NSO) might have beneficial effects in the treatment of diabetic complications. Thirty-two mature male Wistar rats were equally divided into four experimental groups: control, control NSO 2 mL/kg, streptozotocin- (STZ-) induced diabetic, and diabetic (STZ-induced) treated with oral NSO 2 mg/kg for 30 days. Fasting blood glucose (FBG), insulin, and lipid profile levels were determined. Pancreatic and hepatic tissues were used for catalase and GSH. Histopathology, hepatic glycogen contents, insulin immunohistochemistry, and pancreatic islet morphometry were performed. NSO 2 mL/kg was noticed to decrease (P<0.05) FBG and increase (P<0.05) insulin levels in diabetic rats than in diabetic nontreated animals. Lipid profile showed significant (P<0.5) improvement in diabetic rats that received NSO 2 mL/kg than in the diabetic group. Both pancreatic and hepatic catalase and GSH activities revealed a significant (P<0.05) increment in the diabetic group treated with NSO than in the diabetic animals. NSO improved the histopathological picture and hepatic glycogen contents of the diabetic group as well as increased (P<0.05) insulin immunoreactive parts % and mean pancreatic islet diameter. NSO exerts ameliorative and therapeutic effects on the STZ-induced diabetic male Wistar rats.